Perfil genético da biodiversidade da Baía de Aratu, Bahia, Brasil: aplicação do metabarcoding de DNA ambiental - Santiago, Mattheus Luís Alves (2024)
Aratu Bay, located in the Bay of All Saints, Bahia, Brazil, is an inlet that houses estuarine ecosystems and mangroves, known for their high biodiversity and socio-economic relevance. These ecosystems play a crucial role in maintaining environmental health, serving as breeding and feeding grounds for various marine species. The bay sustains local fishing communities and has significant economic importance due to the presence of one of the main industrial ports in the region, being a strategic center for commercial and logistical activities. However, it faces strong pressures due to intense urbanization, industrialization, and maritime traffic. This study aimed to assess the biodiversity of Aratu Bay using the environmental DNA metabarcoding technique. The research was structured into three main areas: i) Evaluation of ichthyofauna biodiversity using the 12S rRNA gene; ii) Analysis of eukaryotic biodiversity and the role of environmental DNA in detecting native and exotic species through the 18S rRNA gene; iii) Investigation of prokaryotic community diversity using the 16S rRNA gene. By using 12S rRNA metabarcoding in the study of ichthyofauna, it was possible to detect marine fish species, ranging from mangrove species to oceanic species, including some not previously documented in the region. The analysis of eukaryotes, through the 18S rRNA gene, revealed a diverse community, with the presence of potentially invasive non-indigenous species, highlighting the importance of continuous monitoring to control bioinvasions. The study of prokaryotic communities, using the 16S rRNA gene, showed a significant diversity of functional groups, from pathogenic to bioremediators, emphasizing the essential ecological role of these microorganisms for the environmental quality of the bay. Finally, the metabarcoding technique proved to be highly effective in providing a comprehensive view of biodiversity, confirming itself as an efficient methodology for monitoring in complex coastal ecosystems. This study not only explored the use of this technology in Aratu Bay but also created an essential starting point for future research and conservation actions, solidifying its pioneering role in the region.